Oribatid mites (Acari, Oribatida) of various habitats in southern Andalusia (Spain) - Seniczak, Stanisław; Seniczak, Anna (Biological Letters, 2011)
Oribatid mites were investigated in some habitats (litter under cypress, pine and larch trees, and patches of grasses, mosses and lichens) in southern Andalusia (Spain) in August 2005. The studied communities of oribatid mites were rather poor in terms of abundance and species diversity. The density of mites in cypress litter from the mountains (Granada, Ronda) was distinctly higher than in the coastal area (Benalmádena), which was probably caused by climatic conditions. The Oribatida achieved the highest density in grassy patches in Granada, but most species occurred in cypress litter from Ronda. Among oribatid species, Oribatula frisiae reached the highest density; also O. tibialis and Haplochthonius simplex were relatively abundant. Some species of Oribatida were rich in juveniles, but the age structure of species greatly depended on the kind of litter.